A Metachronous, Atypical, Multifocal Renal Oncocytoma with a Concomitant Renal Cell Carcinoma of the Contralateral Side and Bilateral Multifocal Oncocytomas: Two Case Reports and Review of Literature - Maximilian Burger; Stefan Denzinger; Thomas Filbeck; Arndt Hartmann; Wolfgang Rößler; Christina Hammerschmied (The Scientific World Journal)
We present one case of a metachronous, atypical, multifocal renal oncocytoma with a concomitant chromophobe renal cell carcinoma (RCC) of the contralateral side and one case of bilateral and multifocal oncocytomas. Oncocytomas are benign renal tumours that rarely appear bilateral or multifocal or with coexisting RCC. A common pathogenic denominator of oncoytomas and RCC is being discussed. The first case was a 63 years old patient presenting with a history of nephrectomy for a pT1 G1 pN0 R0 papillary RCC 4 years prior to presentation, showed two tumours of a singular kidney. Upon nephron-sparing surgery one typical and one atypical oncocytoma with an invasion of the perinephric fat were found. Comparative genomic hybridisation was performed. Both tumours revealed genetic alterations with loss of genetic material on chromosome 1p. The second case was a 62 years old patient presenting with multifocal and bilateral renal tumours of undeclared dignity upon imaging. During open exploration all tumours could be removed by nephron-sparing surgery and were identified as oncocytomas. Again comparative genomic hybridisation was performed. All 4 tumours revealed genetic alterations with loss of genetic material on chromosome 1p, one of the tumours an additional loss of chromosome 10.